Plant breeders' rights - Lončar Gordana (Selekcija i Semenarstvo)
A plant breeder's right is a form of intellectual property specifically created for plant varieties. The Convention of the International Union for the Protection of New Plant Varieties (UPOV), adopted in 1991, is a document that sets international standards for the protection of intellectual property on plant varieties. By acceding to this Convention, Serbia decided to respect its principles, and accordingly adopted a harmonized Law on the Protection of Plant Breeders Rights. The principles contained in the text of the Convention are the only binding ones for the members of the Union. In order to determine the guidelines for the understanding of certain provisions of the Charter of the Convention, a series of explanatory documents was adopted through the negotiations of the members with the active role of observers represented by representatives of breeders and producers. This paper presents Explanatory Notes which explain the provisions of the Convention concerning the scope of rights. The conditions and restrictions that can be set by the breeder with regard to using of reproductive material of the variety are listed. Then, directions to understand articles on compulsory and optional exceptions to the breeders rights were presented. The UPOV Convention does not provide a definition of propagated material nor harvested material. In order to better understand what could be considered as propagating material under the 1991 Act of the UPOV Convention, the list of non-exhaustive examples of factors that have been considered by members of the Union in relation to whether material is propagating is given in the paper. As far as the harvested material is concerned, a clarification is given when it can be concidered propagative material. In this connection the expressions: "reasonable opportunity" "unauthorized use" are also clarified. Finally, as a significant part of the scope of rights, the provision on the exhaustion of rights was presented. After having presented the main provisions of the Convention on the scope of plant breedes right, it is emphasized that this protection system provides opportunities to fulfill the goals that breeders strive for: to engage in further work on the creation of new varieties. It is necessary for persons who create new varieties and persons who use them to become aware of the existence of intellectual property when thinking about varieties The author is suggesting that in order to use the plant breeders rights successfully it is important to understand the nature and the scope of these rights.